THE DRYING PERFORMANCE AND POST-DRYING QUALITIES OF Eucalyptus saligna EXPOSED TO INTERMITTENT AND CONTINUOUS DRYING - Yuniarti, Karnita; Ozarska, Barbara; Brodie, Graham; Harris, Gerry; Waugh, Gary (Association of Indonesian Forestry and Environment Researchers and Technicians, 2020)
Eucalyptus saligna tends to develop defects during its drying process, thus limiting its use as construction or furniture material. Intermittent drying, which applies non-heating phases between heating phases, has the potential to overcome this issue. This study evaluated the effects of 3 intermittent and 1 continuous schedule on the species’ drying performance and post-drying qualities. The results showed that the boards from all intermittent schedules exhibit significantly slower drying rates (from -9.4x10-3 /hour to -1.57 x10-2 /hour) than those from the continuous schedule (from -5.12 x10-2 /hour to -1.03 x10-2 /hour). The intermittently-dried boards also developed lower collapse depth (1.162-2.032 mm) than the continuously-dried boards (5.12 mm). Nevertheless, applying higher temperature than that used in the continuous schedule, during the heating phase of the intermittent schedule, potentially increased the moisture gradient, residual drying stress, end check length, internal check percentage, and spring depth.